Earning the Rockies : how geography shapes America's role in the world - Kaplan, Robert D., 1952- (Random House, 2017)
"As a boy, Robert Kaplan recalls his father driving trucks across the country to earn a living for his family, a man who witnessed and understood America from a ground-level perspective. In Earning the Rockies, Kaplan undertakes his own cross-country journey to recapture an appreciation and understanding of American geography that is often lost in the jet age. Along the way, he witnesses both prosperity and decline--increasingly cosmopolitan cities that benefit from globalization, impoverished small towns abandoned by the same--and paints a bracingly clear portrait of America today, including the anger and alienation that is currently giving rise to Trump and Sanders candidacies. Kaplan lays bare the roots of American greatness--the fact that we are a nation, empire, and continent all at once--and how westward expansion shaped our national character, and should shape our foreign policy"--Provided by publisher.